EZH-2 expression and prognostic significance in patients with low-grade non-Hodgkin lymphoma - Meryem Şener; Hüseyin Derya Dinçyürek; Nazlı Totik; Emine Kılıç Bağır; Semra Paydaş; Emel Gürkan (Scientific Reports)
Abstract EZH-2 overexpression or mutation is associated with various cancers, and there is a substantial academic literature on the role of EZH-2 and its mutant alleles in the pathogenesis of B-cell non-Hodgkin lymphomas (NHLs). The objective of the study was to examine the expression of EZH-2 in patients with low-grade NHL and to assess the effect of this expression on prognosis. The study included 140 pathologically diagnosed indolent NHL cases that met the established inclusion and exclusion criteria. The study assessed a number of factors, including age at diagnosis, gender, histological type of tumor, region of involvement, clinical stage, treatments received, response to treatment, final disease status, and EZH-2 expression rate. The risk of death is 1.87 times higher in patients with EZH-2 positivity (≥ 30% staining density ) for overall survival, while for disease-free survival, the risk of relapse or disease progression is 1.81 times higher in patients with EZH-2 positivity. EZH-2 positivity has been identified as an independent risk factor that significantly reduces survival, thereby worsening prognosis. These findings suggest that EZH-2 expression may be a valuable prognostic marker in indolent NHLs and may help guide treatment decisions in high-risk patient subgroups.